A Hybrid Modelling for Both Pressure-Dependent and Volume-Based Demand in Pressure-Driven Analysis - João Muranho; Joaquim Sousa; Ana Ferreira; Alfeu Sá-Marques; Abel Gomes (Engineering Proceedings)
Water distribution network (WDN) simulation models are usually classified as demand-driven or pressure-driven, depending on whether the demands are independent of or dependent on network pressures, respectively. In real-world networks, both types of demands coexist in the same building. This paper presents a hybrid modelling approach that combines volume-based and pressure-dependent demands in the same model, allowing for different pressure–demand relationships. This hybrid modelling approach is intended to produce more realistic results when modelling WDNs, and it was implemented in WaterNetGen, an EPANET extension.